Metabolic Profile of the Genome-Reduced Bacillus subtilis Strain IIG-Bs-27-39: An Attractive Chassis for Recombinant Protein Production - Aguilar Suárez, Rocío; Kohlstedt, Michael; Öktem, Ayşegül; Neef, Jolanda; Wu, Yuzheng; Ikeda, Kaiya; Yoshida, Ken-Ichi; Altenbuchner, Josef; Wittmann, Christoph; van Dijl, Jan Maarten (ACS Synthetic Biology, 2024)
The Gram-positive bacterium Bacillus subtilis is extensively used in the industry for the secretory production of proteins with commercial value. To further improve its performance, this microbe has been the subject of extensive genome engineering efforts, especially the removal of large genomic regions that are dispensable or even counterproductive. Here, we present the genome-reduced B. subtilis strain IIG-Bs-27-39, which was obtained through systematic deletion of mobile genetic elements, as well as genes for extracellular proteases, sporulation, flagella formation, and antibiotic production. Different from previously characterized genome-reduced B. subtilis strains, the IIG-Bs-27-39 strain was still able to grow on minimal media. We used this feature to benchmark strain IIG-Bs-27-39 against its parental strain 168 with respect to heterologous protein production and metabolic parameters during bioreactor cultivation. The IIG-Bs-27-39 strain presented superior secretion of difficult-to-produce staphylococcal antigens, as well as higher specific growth rates and biomass yields. At the metabolic level, changes in byproduct formation and internal amino acid pools were observed, whereas energetic parameters such as the ATP yield, ATP/ADP levels, and adenylate energy charge were comparable between the two strains. Intriguingly, we observed a significant increase in the total cellular NADPH level during all tested conditions and increases in the NAD+ and NADP(H) pools during protein production. This indicates that the IIG-Bs-27-39 strain has more energy available for anabolic processes and protein production, thereby providing a link between strain physiology and production performance. On this basis, we conclude that the genome-reduced strain IIG-Bs-27-39 represents an attractive chassis for future biotechnological applications.